Cardiotocography monitoration in antepartum care: analysis of controls. (30th September 2020) - Napolitani, M; Kundisova, L; Giannini, B; Moirano, F; Alaimo, L; Nante, N
Abstract: Introduction: WHO does not recommend the routine prenatal cardiotocography (CTG) during pregnancy to improve maternal and perinatal outcomes. Instead, Italian guidelines consider CTG after the 41st week of pregnancy to be useful. The aim of this work was to identify the variables associated with CTG performed before the 40th week. Materials and Methods: A retrospective study was conducted at the Hospital of Siena (Italy), all females that accessed to CTG from 2016 to 2018 was included. The variables were: nationality, pregnancy associated pathology(PAP), gestational age(GA), parity, type of access (urgent/programmed), n° of accesses, active fetal movements (AFM), amniotic fluid index (AFI) and necessity of recovery. The statistical analysis was carried out using Stata 12. Results: The women included were 4010, mean age was 32.8±5.6 years (75% Italian; 62.4% primiparous). A mean GA was 38 ± 3 weeks; 47.5% had one access, 27% two accesses, 14% three accesses. The 22% were urgent accesses, 11.5% had PAP (70% diabetes mellitus). The 58% showed up before the 40th week, the probability was higher for non-Italian women (OR 1.3), multiparous (OR 1.32), women with urgent access (OR 7.9) and women with PAP (OR 3.4). In 5.4% the CTG was altered, 23% had absent AFM and 2% had alterated AFI. Females that came before 40th week were more likely to have absent AFM (OR 4.5) and AFI (OR 2). The 3% needed an immediate hospitalization, mainly in non-Italian (OR 1.7), urgent accesses (OR 4.4), those that came before 40th week (OR 2.44), absent AFM (OR 21.8), and altered AFI (OR 15.8), Conclusions: Our analysis shows the association between precocious access to CTG and urgent medical condition and PAP as expected, but also with other variable as parity and nationality. The low GA without an indication of high risk at the moment of the access suggests the possible overmedicalization of pregnancy. It seems useful to review clinical practices to ensure obstetric care close to best practice. Key messages: As literature reports, to avoid overmedication of pregnancy cardiotocography should not be performed before the 41st week of pregnancy. In some situations the CTG is anticipated and for this reason it seems useful to review the clinical practices implemented in order to ensure obstetric care close to best practice.